Situational Analysis of Human and Wildlife Conflicts at the Periphery of Forêt des Marais Tanoe-Ehy at the East of Côte d’Ivoire - Lydie , Kouao Marthe; Anthelme , Gnagbo (Emerging Issues in Environment, Geography and Earth Science Vol. 2, 2023)
The goal of this article is to define HWC at the FMTE's Forêt des Marais Tanoé-Ehy (FMTE) border to improve public awareness of interactions between people and wildlife near forests in Cote d'Ivoire. The long-term survival of some of the world’s most iconic species, including elephants and tigers, is at risk from a significant and escalating threat: human-wildlife conflict. Human-wildlife conflict is when encounters between humans and wildlife lead to negative results, such as loss of property, livelihoods, and even life. Defensive and retaliatory killing may eventually drive these species to extinction. Crops are more often attacked in Côte d'Ivoire in accordance with animal species' preferred diets. As a result, a diverse range of species, including rodents, birds, predators, and bush pigs, are linked to crop assaults. Certain species of these animals, such as cane rats (Thryonomys swinderianus), monkeys (Cercopithecus sp.), and bush pigs (Potamochoerus porcus), are more active and can result in large losses for farmers. All of these crimes against animals cause some of the local community to harbor enmity toward them. In order to handle these disputes, which have been shown to have a detrimental impact on both biodiversity and food security, in a sustainable manner, the State of Côte d'Ivoire must make crop protection techniques widely known to the populace.